2018
DOI: 10.1042/cs20180758
|View full text |Cite
|
Sign up to set email alerts
|

Urinary angiotensinogen predicts progressive chronic kidney disease after an episode of experimental acute kidney injury

Abstract: One of the major obstacles to prevent AKI-CKD transition is the lack of effective methods to follow and predict the ongoing kidney injury after an AKI episode. In the present study, we test the utility of urinary angiotensinogen (UAGT) for dynamically evaluating renal structural changes and predicting AKI-CKD progression by using both mild and severe bilateral renal ischemia/reperfusion injury mice. UAGT returns to pre-ischemic levels 14 days after mild AKI followed by kidney architecture restoration, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…A critical translational step in monitoring patients after AKI would be development of specific biomarkers of AKI-CKD transition. Indeed, several have been proposed and recently reviewed (Wen and Parikh 2021 ); particularly hopeful may be urinary angiotensinogen, as this marker could also potentially be used to guide renin-angiotensin system based therapy (Cui et al 2018 ). Thus, it is reasonable to speculate that with the right data, perioperative providers may be able to influence the course of AKI-CKD transition in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A critical translational step in monitoring patients after AKI would be development of specific biomarkers of AKI-CKD transition. Indeed, several have been proposed and recently reviewed (Wen and Parikh 2021 ); particularly hopeful may be urinary angiotensinogen, as this marker could also potentially be used to guide renin-angiotensin system based therapy (Cui et al 2018 ). Thus, it is reasonable to speculate that with the right data, perioperative providers may be able to influence the course of AKI-CKD transition in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that urinary AGT is an encouraging biomarker to predict AKI or CKD progression [28]. Using a murine bilateral renal ischemia/reperfusion injury model and a prospective cohort study of 20 pa-tients with acute tubular necrosis, Cui and colleagues found that urinary AGT can dynamically detect renal structural recovery following AKI [29]. However, additional studies are required to determine urinary AGT ability to predict early pediatric AKI-CKD transition.…”
Section: Noninvasive Biomarkers For Monitoring Aki To Ckd Progressionmentioning
confidence: 99%
“…Angiotensinogen (AGT) is an amino acid that plays an important role in the renin -angiotensin system (RAS) and leads to the formation of angiotensin I. It is produced in the kidney by proximal tubule cells and thick ascending limb of Henle (61). Due to its high molecular weight (65 kD), it is not filtered (62).…”
Section: Introductionmentioning
confidence: 99%
“…Detection in urine is due to intra-renal RAS origination rather than systemic RAS activation and it occurs by being released to the tubular lumen (62,63). uAGT is upregulated in tubular cells after AKI and correlated with intra-renal RAS activation and severity of kidney damage (61,64). uAGT is a biomarker indicating kidney damage that can be used for early detection of AKI and prediction of chronic kidney disease earlier than SCr and proteinuria (65)(66)(67), as well as to estimate the probability of recovery from AKI (61).…”
Section: Introductionmentioning
confidence: 99%